Enhanced Effectiveness on Phenol Removal by MgCr-LDH/Microcrystalline Cellulose Composite and Regeneration Study with Green Desorption Reagent - Nova Yuliasari; Alfan Wijaya; Risfidian Mohadi; Aldes Lesbani (Science and Technology Indonesia, 2023)
Modified MgCr-LDH with microcrystalline cellulose (MgCr/MCC) was successfully prepared by the coprecipitation method and characterized using XRD, FT-IR, and BET analyses. MgCr/MCC showed an increase in surface area from 21.51 to 26.056 m2/g. The material was tested as an adsorbent for the removal of phenol. MgCr/MCC showed an increase in adsorption capacity from the initial material of 24.631 to 58.480 mg/g. The optimum pH was at pH 9 and the adsorption process’s equilibrium time is 70 minutes. The correlation coefficients on the kinetics and isotherm parameters show that phenol removal follows the pseudo second order (PSO) and Langmuir models with spontaneous and endothermic adsorption processes. The regeneration ability of MgCr/MCC material using the water-assisted ultrasonic system as a green desorption reagent was 3 cycles with a percent regeneration efficiency of 39.45%.